Standard Dictionary of English Language: Volume Two: Lobate Through Z - Wilfred Funk; Albert H. Marckwardt; Frederic G. Cassidy; S. I. Hayakawa; James B. Mcmillan (New York Funk and Wagnalls Company, 1969)
International Edition
Funk & Wagnalls dictionaries, family of English-language dictionaries noted for their emphasis on ease of use and current usage.
Keywords: Languages (3GddZGJs; General